Analysing the optimum effect of the human hair waste as fiber reinforcement in M20 grade concrete - Bhishma Raj Shigu,; Iswar Man Amatya,; Gokarna Bahadur Motra, (Journal of Innovations in Engineering Education, 2023)
Human hairs are considered as unused waste material which are non-degradable and are found in abundance in urban cities like Kathmandu. Human hair as a solid waste has multifaceted environmental problems and the main aim of this study is to utilize such unused human hair to enhance the properties of concrete. Human hair as a fiber possesses high tensile strength property and can be used in concrete to enhance compressive and tensile strength properties of concrete.In this experimental study, experiment was performed on M20 grade concrete mix with varying percentages of human hair fiber i.e., 0%, 0.50%, 1.00%, 1.25%, 1.50%, 1.75 and 2.00% by weight of cement to analyze the compressive and flexural strength. To analyze the workability of the mixes slump test was performed. Test results showed that compressive strength and flexural strength increased up to 1.50% of human hair fiber content and decreased beyond 1.5% which shows that optimum HHF content for our study on M20 grade of concrete is 1.5%. Hence, human hair can be used in concrete to enhance its compressive and flexural properties and will be the alternative way of salon hair waste management.